Preventing injuries in basketball - Klein, C.; Luig, P.; Henke, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Approximately 1.7 million citizens within the EU-27 area play basketball regularly. Recent research shows an injury incidence of 3-6 injuries/1000h. Thus, one has to expect at least 720,000 basketball-related injuries a year causing direct medical costs of 500 million. The purpose of this study, which is part of the EU funded project "Safety in Sports", is to illustrate smart ways how to prevent basketball injuries in a sustainable manner Methods A structured literature search for relevant publications of the period 1990-2009 was performed. The identified sources were furthermore graded by a panel of basketball injury prevention experts (n=20) in terms of their effectivity, applicability and acceptance. This evaluation process led to a number of encouraging recommendations which were adapted to the national demands and have been pilot implemented into two national basketball associations within the FIBA-Europe. Results 70 sources dealing with 108 preventive recommendations were identified and divided into four categories - (1) Training/Physical Preparation, (2) Technical/Political Approaches, (3) Equipment/Facilities and (4) Medical/Non-medical Support. The great majority (47 %) is focusing on the first category, which is also judged most valuable by the expert panel. These preventive measures focus on basic physical preparation, structured warm-up routines, basic and advanced technique training and neuromuscular training. Further important preventive measures are given in the category Equipment/Facilities. These recommendations focus on ankle injury prevention via external ankle stabilisation as well as custom-made mouth guards to reduce dental injuries. Discussion Basketball associations and clubs should follow a pro-active strategy as to the risk of injury and communicate with members and the general public openly about risks involved and necessary measures to be taken by clubs and individuals. Players should be provided with educational materials presenting basic exercises. It is recommended to have all national associations to include an injury prevention module in their trainer education curriculums and to designate an official staff member as `safety promotion ambassador` of the federation. Such a pro-active approach will also contribute to the positive image of the game and will help to attract new members.